City size, administrative rank, and Rural–Urban migration in China - Chengri Ding; Mingsheng Wang; Zhongxing Guo; Ning Chen (Journal of Urban Management, 2024)
This study investigates the effects of city size and administrative rank on rural–urban migration in China and examines the factors that influence the city size effect. We focus on unemployed while job-seeking migrants. Using data from the China Migrants Dynamic Survey for 2016 and 2017, we find that city size and administrative rank positively influence the destination of rural–urban migrants. Furthermore, we conclude that individual characteristics and home province features influence the city size effect. Young, unmarried, educated, and first-time migrants tend to choose big cities. Migrants from provinces without a primate city tend to move across provincial boundaries, implying that big cities are destinations. Moreover, the city size effect positively correlates with urban concentration and urbanization. Finally, we noted that first-time migrants tend to select a big city to migrate.